Identificação da presença de osteoporose e fraturas vertebrais na doença pulmonar obstrutiva crônica - Ruas, Gualberto (Universidade Federal de São Carlos, 2010)
Introduction: Osteoporosis is a progressive disease with a significant reduction in bone mineral density (BMD) contributes to the emergence of osteoporotic vertebral fractures, thereby directly interfering with the quality of life of patients with chronic obstructive pulmonary disease (COPD). Objectives: Detection of osteoporosis, vertebral fractures and pain intensity in the regions of the spine in men with moderate to severe COPD, but also whether there is any relationship between the variables studied and the degree of pulmonary obstruction. Methods: We studied 34 males with COPD (COPDG) and 33 healthy sedentary men (CG), through the bone densitometry and radiographs of the thoracic and lumbar spine. Results: There were no significant differences between groups in clinical trials that were within normal limits and anthropometric data. The COPDG showed lower values in the spirometric variables, BMD and T-score at lumbar spine, femoral neck and trochanter compared with the CG (p<0,05; Student t test), moreover, there was no correlation between FEV1 and BMD and T-score (Pearson correlation, p>0,05). It was found that 28 (83%) of individuals COPDG have osteoporosis, and 20 individuals (59%) presented with moderate obstruction of the lumbar spine, 0l (3%) in the femoral neck and 0l (3%) in the trochanter; 4 (12%) with severe pulmonary obstruction in the lumbar spine, 0l (3%) and femoral neck 0l (3%) in the trochanter. Twenty subjects (59%) of COPDG with moderate obstructive pulmonary disease patients with osteoporosis showed osteoporotic vertebral fractures in segments T5, T7, T9, T11, T12 and L1 grads I and II, 4 (12%) with severe obstructive pulmonary disease patients with osteoporosis at the lumbar spine osteoporotic fractures had grade III between segments T12-L4 (k=0,90;CI: 95%; with k=0,72-1,0) already in the CG 3 subjects had vertebral fractures and osteoarthritis segments T5, T6 and L1 and none had osteoporotic vertebral fractures (k=0,89; CI: 95% with k=0,72-1,0), the pain intensity of 3 individuals COPDG obstructive lung conditions who had osteoporosis and osteoporotic vertebral fractures grade III, reported presence of pain intensity "light" in the thoracolumbar region, while 21 had osteoporotic vertebral fractures and 3 asymptomatic individuals with CG not osteoporotic vertebral fractures and arthritis reported moderate pain intensity in the lumbar region. Conclusions: We conclude that individuals with moderate to severe COPD also had pulmonary involvement, decreased BMD and osteoporotic vertebral fractures, which indicates the need to adopt measures that take into account the prevention of osteoporosis in these patients and early diagnosis of this. Still, considering the entirety of the individual's needs, these must be assessed and addressed in establishing programs of physical therapy intervention to avoid future complications such as worsening or appearance of new fractures and thus promoting the improvement of functional capacity and quality of life.
Keywords: Fisioterapia; Osteoporose; Coluna vertebral - lesões; Doença Pulmonar Obstrutiva Crônica (DPOC); Densidade mineral óssea; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL